THE ROLE OF PSYCHODIAGNOSTICS IN IDENTIFYING EMOTIONAL DISORDERS IN ADOLESCENTS - Pramitha, Aderia; Iskandar Dinata, Konto (International Journal of Multidisciplinary Reseach, 2025)
Adolescence is a developmental phase characterized by complex biological, psychological, and social changes, making individuals vulnerable to emotional disorders such as anxiety, depression, and affective instability. Early identification of these conditions is crucial to prevent long-term negative impacts, particularly on academic achievement, social relationships, and overall mental health. This article aims to analyze the role of psychodiagnostics as a systematic approach to identifying emotional disorders in adolescents. The method used was a literature review of 20 relevant national and international journals on psychological assessment, psychometrics, and adolescent development. The results showed that the use of psychodiagnostic tools such as projective tests, personality inventories, emotion scales, and clinical interviews can provide a comprehensive picture of adolescents' emotional states. Furthermore, the integration of multiple instruments has been shown to increase diagnostic accuracy. These findings confirm that psychodiagnostics plays a crucial role in the early detection of emotional disorders and serves as the basis for developing more targeted psychological interventions. Thus, psychodiagnostics is a crucial component in efforts to prevent and treat emotional problems in adolescents.